2020
DOI: 10.1108/mmms-09-2019-0165
|View full text |Cite
|
Sign up to set email alerts
|

Activation energy impact on radiated magneto-Sisko nanofluid flow over a stretching and slipping cylinder: entropy analysis

Abstract: PurposeThe purpose of this article is to analyze the heat and mass transfer with entropy generation during magnetohydrodynamics (MHD) flow of non-Newtonian Sisko nanofluid over a linearly stretching cylinder under the influence of velocity slip, chemical reaction and thermal radiation. The Brownian motion, thermophoresis and activation energy are assimilated in this nanofluid model. Convective boundary conditions on heat and mass transfer are considered. The physical model may have diverse applications in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…It is observed here that drag force decreases for large values of magnetic and curvature parameters. Sarkar et al 56 examined the impact of activation energy on a hydromagnetic Sisko nanofluid on a linear stretching cylinder. Lately, researchers have pondered on the fluid flows with activation energy [57][58][59][60] .…”
Section: Reaction Rate Constantmentioning
confidence: 99%
“…It is observed here that drag force decreases for large values of magnetic and curvature parameters. Sarkar et al 56 examined the impact of activation energy on a hydromagnetic Sisko nanofluid on a linear stretching cylinder. Lately, researchers have pondered on the fluid flows with activation energy [57][58][59][60] .…”
Section: Reaction Rate Constantmentioning
confidence: 99%
“…With the significance of the variable magnetic field, the properties of the micropolar fluid on distinct mediums were explored by Nadeem et al 14 Through a stretched, slender medium, the thermal analysis and flow mechanism based on magnetic properties in a fluid containing distinct nanoparticles were addressed by Elsebaee et al 15 Recent studies on the magnetized flow of hybrid nanofluids can be found in ref. 16–24.…”
Section: Introductionmentioning
confidence: 99%
“…The heightening in heat transference is noticed for the higher melting parameter. Sarkar et al [ 38 ] scrutinized the energy and mass transition with entropy generation and non-Newtonian Viscoelastic nanofluid flowing over a stretching cylinder. Alsallami et al [ 39 ] have used the rotating disk for the computation of activation energy and entropic generation due to the Marangoni Maxwell nanofluid flow.…”
Section: Introductionmentioning
confidence: 99%